Ectopic adrenocorticotrophic hormone syndrome in a 10-year-old girl with a thymic neuroendocrine tumor: a case report - Aldhoon-Hainerová, Irena; Kosák, Mikuláš; Kršek, Michal; Zogala, David; Pacak, Karel (BMC endocrine disorders, 2024)
BACKGROUND: Thymic neuroendocrine tumor as a cause of Cushing syndrome is extremely rare in children. CASE PRESENTATION: We report a case of a 10-year-old girl who presented with typical symptoms and signs of hypercortisolemia, including bone fractures, growth retardation, and kidney stones. The patient was managed with oral ketoconazole, during which she experienced adrenal insufficiency, possibly due to either cyclic adrenocorticotropic hormone (ACTH) secretion or concurrent COVID-19 infection. The patient underwent a diagnostic work-up which indicated the possibility of an ACTH-secreting pituitary neuroendocrine tumor. However, after a transsphenoidal surgery, the diagnosis was not confirmed on histopathological examination. Subsequent bilateral inferior petrosal sinus sampling showed strong indications of the presence of ectopic ACTH syndrome. Detailed rereading of functional imaging studies, including 18F-FDG PET/MRI and 68Ga DOTATOC PET/CT, ultimately identified a small lesion in the thymus. The patient underwent videothoracoscopic thymectomy that confirmed a neuroendocrine tumor with ACTH positivity on histopathological examination. CONCLUSION: This case presents some unique challenges related to the diagnosis, management, and treatment of thymic neuroendocrine tumor in a child. We can conclude that ketoconazole treatment was effective in managing hypercortisolemia in our patient. Further, a combination of functional imaging studies can be a useful tool in locating the source of ectopic ACTH secretion. Lastly, in cases of discrepancy in the results of stimulation tests, bilateral inferior petrosal sinus sampling is highly recommended to differentiate between Cushing disease and ectopic ACTH syndrome.
Keywords: Humans; dítě; neuroendokrinní nádory; Child; Cushingův syndrom; Female; ektopický ACTH syndrom; 68Ga-DOTATOC PET/CT; lidé; Neuroendocrine Tumors; Ectopic Cushing syndrome; Ketoconazole; ketokonazol; 18F-FDG PET/MRI; ACTH Syndrome, Ectopic; ženské pohlaví; Thymus Neoplasms; thymektomie; Cushing Syndrome; Thymectomy; Thymic neuroendocrine tumor; nádory brzlíku